Attitudes towards limited drug prescription rights: A survey of South African chiropractors - Thriya Huluman; Christopher Yelverton; Cynthia Peterson (AOSIS, 2022)
Background: Several surveys that have been published show opinions regarding a change in the scope of chiropractic practice to include prescription rights. Currently, research into the attitudes of South African chiropractors towards having this right is non-existent. Aim: To ascertain the attitudes of South African chiropractors towards the inclusion of drug prescription rights in their scope of practice. Setting: The study was conducted on chiropractors registered with the Allied Health Professions Council of South Africa and members of the Chiropractic Association of South Africa. Method: A self-administrative online questionnaire was developed, and sent via email to all registered chiropractors in South Africa in February 2020. Descriptive statistics were used to analyse the data. Results: The response rate for this study was 15.9% (n = 138). 84% (n =105) were in favour of limited prescription rights for over-the-counter medication. However, 79.6% (n = 98) did not agree to full prescriptions rights for non-musculoskeletal drugs. A total of 33.6% (n = 42) rarely recommended OTC and prescription-based analgesics, muscle relaxants and non-steroidal anti-inflammatory drugs (NSAIDs) to their acute patients and 37.9% (n = 52) rarely recommended these drugs to chronic patients. 68.8% (n = 86) were confident in their knowledge of musculoskeletal drugs and 91.2% (n = 112) agreed on further education and training in pharmacology for those practitioners seeking limited medication prescription rights. Conclusion: The majority of South African chiropractor respondents indicated an interest in expanding their scope of practice to include limited prescription rights. Contribution: These findings could indicate a shift in the attitudes of chiropractors towards drug prescription rights within the profession.